The Effects of Leisure Agricultural Experience Activities on Satisfaction: Empirical Evidence from Different Tourist Styles in Taiwan - Huang, Biing-Wen; Yang, Yu-Chen (Journal of Reviews on Global Economics, 2018)
Leisure agricultural activities play an important role in rural tourism. The research presented in this research was used to investigate the impression of leisure agricultural activities on different groups of tourists. Using the four dimensions of the Experience Economy suggested by Pine and Gilmore (1999), this research analyzes the impacts of entertainment, educational, aesthetic, and escapism experiences on tourist satisfaction. The data used in the study were gathered by surveying 374 tourists in the leisure agricultural area of Lugu township in central Taiwan. By using factor analysis and cluster analysis, tourists in this study were categorized into two groups, namely, a ‘deep experience group’ and ‘moderate experience group,’ based on the degree to which they experienced the activities. Through the use of a structural equation model, the empirical results indicated that the correlation between the activities experienced and the degree of satisfaction were distinctive for each group of tourists.